1993
DOI: 10.1080/00207284.1993.11491238
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Group Therapy Outcome for Adult Sexual Abuse Survivors

Abstract: Adult female sexual abuse survivors (N = 148) participated in year-long therapy groups. Demographic, abuse history, initial symptomatology, and group process variables were examined in relationship to group completion and improvement over time. Survivors who had previously been psychiatrically hospitalized were less likely to complete group treatment. Among group completers, significant pretreatment-posttreatment changes were found on measures of locus of control, sexual problems, self-esteem, trauma-related s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 18 publications
6
34
1
Order By: Relevance
“…The d-indices of outcomes immediately following group termination ranged from .30 (Alexander et al, 1989) to 1.38 (Threadcraft & Wilcoxon, 1993). The mean index of the six short-term (less than 20 weeks) group studies was .79 and did not differ significantly from the d-index of the one long-term study evaluated (.66) (Hazzard et al, 1993). The U 3 of the short-term groups was 78.5%, which did not differ significantly from the U 3 of the long-term group (74.5%).…”
Section: Meta-analysesmentioning
confidence: 96%
See 1 more Smart Citation
“…The d-indices of outcomes immediately following group termination ranged from .30 (Alexander et al, 1989) to 1.38 (Threadcraft & Wilcoxon, 1993). The mean index of the six short-term (less than 20 weeks) group studies was .79 and did not differ significantly from the d-index of the one long-term study evaluated (.66) (Hazzard et al, 1993). The U 3 of the short-term groups was 78.5%, which did not differ significantly from the U 3 of the long-term group (74.5%).…”
Section: Meta-analysesmentioning
confidence: 96%
“…& Wilcoxon, 1991;Carver et al, 1989;Hazzard, Rogers, & Angert, 1993;Richter et al, 1997;Roberts & Lie, 1989;Threadcraft & Wilcoxon, 1993). Studies were included if enough data were reported to calculate a Cohen's (1988) d-index, an effect size indicator calculated from reported means or standard deviations or from other outcome statistics (e.g., t-test, F-ratio) to allow for across study comparison.…”
Section: Meta-analysesmentioning
confidence: 99%
“…We found that a better post-treatment status was predicted by fewer initial symptoms and with no previous treatment, a factor that has earlier been associated with rather poor post-treatment status (14). Furthermore, these women may have been relatively amenable to treatment, as almost all were married or cohabiting, a status that has been associated with increased posttreatment outcome (15).…”
Section: Discussionmentioning
confidence: 93%
“…Five studies measured the effects within therapy groups. In three of the studies, the outcome was statistically significant improvements concerning self-esteem (Hazzard, Rogers, & Angert, 1993), self-concept (Threadcraft & Wilcoxon, 1993), and psychosocial functioning (Roberts & Lie, 1989). In two of the studies no improvements occurred concerning self-esteem (Carver, Stalker, Stewart, & Abraham, 1989) and concerning marital adjustment (Paddison, Einbinder, Maker, & Strain, 1993).…”
Section: Group Treatment Studiesmentioning
confidence: 99%
“…Statistically significant improvements were shown for therapy groups concerning interpersonal problems (Cloitre & Koenen, 2001), isolation Studies measuring effects within the trauma group Carver et al (1989) 57 Therapy group TSBI Not improved self-esteem. Hazzard et al (1993) 148 Therapy group ISE Improved self-esteem. Paddison et al (1993) 41 Therapy group MAS, IOES Not improved marital relations, intrusion and avoidance.…”
Section: Group Treatment Studiesmentioning
confidence: 99%